The types and durations of antiplatelet drugs for symptomatic vertebrobasilar artery stenosis: a retrospective study - Liu, Xi; Zhong, Guanghong; Gu, Hongli; Wen, Yangchun; Zhong, Xiaojing; Zhang, Jia; Xie, Ying (Frontiers in Neurology, 2025)
BackgroundPatients with symptomatic vertebrobasilar artery stenosis not only experience a first stroke event, but also have a high risk of recurrent stroke. Even though interventional techniques have been widely used in the treatment of cerebral infarction, the therapeutic efficacy for symptomatic vertebrobasilar artery stenosis patients are not superior to that achieved with simple drug therapy. However, the optimal choice of drugs and the duration of their use in a pure drug regimen remain unclear.MethodsThis retrospective study analyzed data from Heyuan People’s Hospital (2021–2023) on patients with vertebrobasilar artery stenosis. Patients were grouped by treatment duration (30/90 days ticagrelor vs. 90 days clopidogrel), all receiving aspirin. Outcomes included ischemic events, bleeding, and complications. SPSS version 22.0 was employed for statistical analysis.ResultsThis study included 217 patients with symptomatic vertebrobasilar artery stenosis. Clinical features and outcomes of efficacy and safety analyses were conducted. No significant differences in baseline data or safety outcomes were found. However, a significant difference in endpoint events was observed within 90 days for specific subgroups of symptomatic intracranial vertebrobasilar artery stenosis and CYP2C19 gene deletion.ConclusionFor patients with symptomatic vertebrobasilar artery stenosis, the ticagrelor plus aspirin regimen may provide an alternative therapeutic option to the aspirin plus clopidogrel bisulfate regimen. Furthermore, this regimen may represent a favored treatment choice for specific patient subpopulations.